A thermally conductive interface material with tremendous and reversible surface adhesion promises durable cross-interface heat conduction. Issue 6 (8th April 2022) - Guo, Cong; Li, Yuhan; Xu, JianHua; Zhang, Qin; Wu, Kai; Fu, Qiang
Abstract : A ternary polyurethane composite with high isotropic thermal conductivity, electrical insulation and temperature-responsive reversible adhesion was synthesized, promising low thermal resistance and durable thermal contact with electronic substrates. Abstract : The dramatic miniaturization and integration of electronic devices call for next-generation thermally conductive interface materials with higher service performance and long-term stability. In addition to enhancing the inherent thermal conductivity of materials, it is noteworthy to pay attention to the thermal contact resistance. Herein, we synthesized a polyurethane with hierarchical hydrogen bonding to realize high surface adhesion with substrates; another key was incorporating aluminum oxide modified by a deformable liquid metal to improve the thermo-conductive capability and offer the freedom of polymeric segmental motions. These molecular and structural designs endow the composite with high isotropic thermal conductivity, electrical insulation and temperature-responsive reversible adhesion, which enable low thermal resistance and durable thermal contact with substrates without the need for external pressure.